THE EFFECT OF PSYCHODRAMA ON ANXIETY LEVELS AND STRESS COPING STYLES IN ACADEMICIANS - Esra Porgali Zayman; Bircan Kirlangic Simsek (Medicine Science, 2023)
This study aimed to investigate the effects of psychodrama on stress and coping with stress in people working as medical doctors and nurses academicians. This study confirmed whether psychodrama could be effective on stress and coping mechanisms for nurses and medical doctors academicians. Individuals were evaluated by the state and continuity anxiety scale, the stress coping style scale, the Hamilton anxiety scale, and the Hamilton depression scale. The Statistical Program for Social Sciences-SPSS for Windows, version 22.0, was used for statistical analysis (SPSS Inc., Chicago, IL, USA).Data are given as mean (standard deviation) and number (percentage). To test the normal distribution compliance of the data, the Kolmogorov Smirnov test, T test for independent groups in normally distributed data with two groups, ANOVA test for data with more than two groups with normal distribution, and Mann Whitney U test for data with normal distribution was used. A statistically significant difference was found in the pre-test and post-test average scores of the applied scales. Practice Implications It is recommended that this study be performed with a more homogeneous patient group. It was found that psychodrama significantly affected stress and stress coping styles in individuals who work as academicians. It was found that psychodrama significantly affected stress and stress-coping styles in individuals. The most important limitation of our study was that the participants were in the same academic community. [Med-Science 2023; 12(1.000): 253-8]